Knowledge of health care providers in the Kindu health zone about the threat of Ebola disease - Bonny , ASSANI WAKENGE; MUHEMEDI MASKINI Salvador; BARUANI ZAKUNI Theophile; KAMANA LELA Grace; SHINDANO MWAMBA Etienne (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Ebola is one of the notifiable viral haemorrhagic fevers. The occurrence of a known or suspected case of viral haemorrhagic fever must be reported immediately. Between the years 1976 and 2018, DRC recorded 10 epidemics of Ebola viral haemorrhagic fever, the largest of which occurred in the year 2018. Declared by the WHO as a public health emergency of international concern, the 2018 epidemic is considered the most serious in terms of the number of cases and deaths reported since the discovery of the virus on 1 October 2019, with a total of 3197 VHE cases reported, 3083 confirmed cases and 114 probable cases, including 2136 fatal cases (overall case-fatality rate of 67%). The general objective is to assess the level of knowledge of the health staff of the Kindu health zone about the Ebola virus disease. Through a descriptive cross-sectional study of 70 health care providers based on a questionnaire survey the results revealed that 6 out of 10 health care providers surveyed have limited knowledge, about 3 out of 10 respondents have affordable knowledge and only about 1 out of 10 respondents have good knowledge. Based on this result, we conclude that the preparatory work for the prevention and containment of Ebola disease in the Kindu health zone is perceived as inadequate by the health care providers.